2007
DOI: 10.1038/sj.clpt.6100102
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Variation in the Adenosine A2A Receptor Gene (ADORA2A) Contributes to Individual Sensitivity to Caffeine Effects on Sleep

Abstract: Caffeine is the most widely used stimulant in Western countries. Some people voluntarily reduce caffeine consumption because it impairs the quality of their sleep. Studies in mice revealed that the disruption of sleep after caffeine is mediated by blockade of adenosine A2A receptors. Here we show in humans that (1) habitual caffeine consumption is associated with reduced sleep quality in self-rated caffeine-sensitive individuals, but not in caffeine-insensitive individuals; (2) the distribution of distinct c.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
181
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(190 citation statements)
references
References 40 publications
6
181
1
2
Order By: Relevance
“…From cognitive performance under sleepdeprivation conditions, it is known that the degree of impairment varies highly among individuals (34). Differences in caffeine effects have been linked to sleep-loss-induced performance impairments (35) and to genetic variants of the adenosinergic system (36,37). Along these lines, we defined two subgroups based on the A 1 AR availability decrease, of which one group showed a strong decline in receptor availability, whereas the other revealed only a minor decline.…”
Section: Discussionmentioning
confidence: 99%
“…From cognitive performance under sleepdeprivation conditions, it is known that the degree of impairment varies highly among individuals (34). Differences in caffeine effects have been linked to sleep-loss-induced performance impairments (35) and to genetic variants of the adenosinergic system (36,37). Along these lines, we defined two subgroups based on the A 1 AR availability decrease, of which one group showed a strong decline in receptor availability, whereas the other revealed only a minor decline.…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism is linked to a expression (Alsene et al, 2003). Rétey and co-workers observed that the 1976T>C polymorphism not only contributes to individual sensitivity to the effects of caffeine on sleep (Rétey et al, 2007), but also affects EEG activity in all sleep/vigilance states. In a case-control study, spectral power in the ~ 7-10 Hz range was shown to be invariably higher in subjects with the C/C genotype than in subjects with the T/T genotype (Rétey et al, 2005).…”
Section: T>c Polymorphism Of Adenosine a 2a Receptor (Adora2a) Genementioning
confidence: 99%
“…An internet survey about self-rated caffeine sensitivity and sleep was recently conducted among 20'343 University students [16]. A total number of 2'308 men and 2'021 women responded (response rate: 21 %).…”
Section: Sleep Durationmentioning
confidence: 99%